The effects of physical exercise on anxiety symptoms of college students: A meta-analysis - Yanru Lin; Wei Gao (Frontiers in Psychology, 2023)
ObjectiveThis study aimed to evaluate the effect of an exercise intervention on improving and alleviating anxiety symptoms in college students with a meta-analytical approach.MethodsSeveral databases (e.g., PubMed, Embase, and the Cochrane Library) were used to search for randomized controlled trials (in short, RCTs) on interventions for physical exercise or aerobic exercise in college students with anxiety symptoms. Stata software, version 16.0, was applied sequentially for traditional meta-analysis, subgroup analysis, and publication bias analysis.ResultsA total of nine papers were included. The total literature effect [SMD = −0.55, 95% CI = −0.76 to −0.35, Z = 5.38 (P < 0.001)] indicated that physical activity had a significant effect on alleviating anxiety. Subgroup analysis also showed that exercise interventions using aerobic exercise or yoga were effective in relieving anxiety (SMD = −0.39, 95% CI = −0.74 to −0.04; SMD = −0.76, 95% CI = −1.14 to −0.39).ConclusionPhysical activity interventions were shown to have a positive effect on alleviating anxiety in college students. Aerobic exercise was found to be the optimal mode.